Vehicle License Plate Detection and Recognition System: A Review - Goyal, Shubh; Dube, Srijan; Mali, Niranjan; Udawant, Prashant (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
There is no fixed recognition system for identifying and recognizing a license plate, it has been discovered. As the texture and writing pattern are not the same hence, the plate design differs from one country to another. Detecting and recognizing vehicle license plates is a common and difficult task. We looked at some strategies for detecting and recognizing license plates in this paper. To recognize and understand the license plate, high-resolution cameras acquire an image of the vehicle.
Keywords: Automatic Number Plate Recognition (ANPR); Optical Character Recognition (OCR); License Plate (LP)